2007
DOI: 10.1002/app.27463
|View full text |Cite
|
Sign up to set email alerts
|

High temperature organic/inorganic addition cure polyimide composites, part 1: Matrix thermal properties

Abstract: Structure-thermal property interrelationships are characterized and reported for organic/inorganic addition cure polyimide composite matrices based on 3,3 0 ,4,4 0 -benzophenone tetracarboxylic dianhydride, the reactive terminal group 4-phenylethynyl phthalic anhydride, and stoichiometric controlled diamine ratios of 1,3-phenylenediamine, 1,4-phenylenediamine, or 4,4 0 -(1,3-phenylenediisopropylidene) bisaniline, combined with bis(p-aminophenoxy) dimethyl silane or an a, x-bis(3-aminopropyl) polydimethylsiloxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…The previous work demonstrates that making the polymer structure organic/inorganic hybrid could effectively address the issue. [9][10][11][12][13][14] Iscoahedral carboranes such as o-, m-, and p-C 2 B 10 H 12 have great thermal and chemical stability due to their stable cage structures and rich boron contents. The thermal stability of polymers could be greatly enhanced by the incorporation of carboranes into the matrices.…”
Section: Introductionmentioning
confidence: 99%
“…The previous work demonstrates that making the polymer structure organic/inorganic hybrid could effectively address the issue. [9][10][11][12][13][14] Iscoahedral carboranes such as o-, m-, and p-C 2 B 10 H 12 have great thermal and chemical stability due to their stable cage structures and rich boron contents. The thermal stability of polymers could be greatly enhanced by the incorporation of carboranes into the matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many researchers dedicated to improve the glass transition temperature of polyimide. Lincoln and coworkers 6 improved the glass transition temperature and mechanical properties of the polyimide by importing diamine siloxane structure into the molecular chain. Lee and coworkers 7 prepared POSS‐PETI oligomers and found that the addition of 3% mass fraction POSS‐PETI can increase the glass transition temperature of resin by nearly 50 K. Seurer and coworkers 8,9 also found that the shape, position and structure of POSS could affect the glass transition temperature of PI.…”
Section: Introductionmentioning
confidence: 99%
“…In those circumstances, high temperatures and repeated thermal cycles require thermal and thermos-oxidative stability of materials at elevated temperatures. In order to improve the thermal or thermo-oxidative stability, polyimide films are usually coated with metal or inorganic oxide protection layer or blended with inorganic fillers [23][24][25][26][27]. However, the mismatching of the coefficient of thermal expansion (CTE) between inorganic coatings and polymer matrices might result in serious troubles such as delamination, curl, or crack after harsh heat shocking [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mismatching of the coefficient of thermal expansion (CTE) between inorganic coatings and polymer matrices might result in serious troubles such as delamination, curl, or crack after harsh heat shocking [28]. Although the addition of inorganic fillers into polymer matrices to form hybrid structures is an effective pathway in enhancing thermo-oxidative stability of polymer materials, the limited filler loadings and the poor miscibility of inorganic fillers and organic matrices are the big issues [26,27,29,30]. Hence, developing intrinsic thermo-oxidative stable polymers is still the desirable pathway.…”
Section: Introductionmentioning
confidence: 99%